Membentuk Kesadaran Sejak Dini: Gaya Hidup Aktif dan Jantung Sehat sebagai Investasi Masa Depan Remaja - Alfiandari, A. Dhini; Sarea, Syahrianti; Paramita, Diah Astini; Damry, Nurul Mufidha; Yusuf, Dewi (MAMMIRI: JURNAL PENGABDIAN MASYARAKAT, 2025)
Cardiovascular disease (CVD) remains one of the leading causes of death in Indonesia, and its prevalence has been increasing among the younger population. Low levels of knowledge and awareness among adolescents regarding the importance of maintaining an active lifestyle for CVD prevention continue to pose challenges in reducing future cardiovascular morbidity. This community service program aimed to enhance awareness among students of SMAN 1 Parepare about active lifestyles and CVD prevention through targeted health education. The program utilized a combination of presentations, poster-based visual education, interactive discussions and Q&A sessions, as well as game-based quizzes to reinforce learning. The implementation resulted in a noticeable improvement in students’ understanding, reflected through their active engagement and correct responses during learning activities. The interactive educational approach was effective in promoting adolescent comprehension of active lifestyle concepts and CVD prevention. These findings suggest that school-based health promotion initiatives can be replicated to strengthen early CVD prevention efforts among Indonesian adolescents.